Lateral root initiation is a probabilistic event whose frequency is set by fluctuating levels of auxin response - Laskowski, Marta (Journal of experimental botany, 2013)
The locations in which lateral roots arise are determined by local peaks of auxin response driven by whole-plant physiology. The architecture of a plant root system adapts it to the conditions in which it grows: large shoot systems demand large root systems, and growth in soils that have low or patchy nutrient distributions is often best managed by non-uniform patterns of root branching. It is not surprising then that the regulation of lateral root spacing is responsive to a wide array of stimuli. Molecular genetic studies have outlined a mechanism by which multiple modules of auxin response in specific cell types drive lateral root initiation. These peaks of auxin responsiveness are functionally controlled by the growth of the plant and the changing environmental conditions it experiences. Thus, the process of lateral root initiation, which depends on strong local auxin response, is globally mediated